2007
DOI: 10.1111/j.1365-2265.2007.03009.x
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function and anti‐thyroid autoantibodies in untreated children with vertically acquired chronic hepatitis C virus infection

Abstract: Our data suggest a role for HCV infection in the development of nonautoimmune thyroid disease in untreated HCV-infected children, confirming previous studies in adults. Clinicians should be aware of thyroid dysfunction even in untreated children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 26 publications
(53 reference statements)
3
36
0
5
Order By: Relevance
“…1.3% had an abnormal thyroid function, who were than referred to an endocrinologist and 98.6% become euthyroid without any therapy this follow up was missing in previous studies [12]. Thus this study confirms previous findings that reversibility of thyroid dysfunction after completion of interferon and ribavirin therapy in hepatitis C virus patients [20,21]. Statistically significant (p-0.003) association was observed between the existence of diabetes and end treatment response of HCV because a positive association between chronic HCV infection and DM has been consistently demonstrated across different ethnicities and geographic regions, in both developed and developing countries [22].…”
Section: Discussionsupporting
confidence: 82%
“…1.3% had an abnormal thyroid function, who were than referred to an endocrinologist and 98.6% become euthyroid without any therapy this follow up was missing in previous studies [12]. Thus this study confirms previous findings that reversibility of thyroid dysfunction after completion of interferon and ribavirin therapy in hepatitis C virus patients [20,21]. Statistically significant (p-0.003) association was observed between the existence of diabetes and end treatment response of HCV because a positive association between chronic HCV infection and DM has been consistently demonstrated across different ethnicities and geographic regions, in both developed and developing countries [22].…”
Section: Discussionsupporting
confidence: 82%
“…However, recently, several studies have confirmed an association of hepatitis C virus (HCV) infection with AITD both in adults [39,40] and in children [41].…”
Section: Hcvmentioning
confidence: 98%
“…HCV can infect human thyrocytes resulting in production of proinflammatory cytokines, which may enhance the autoimmune response (87). Indeed, thyroid antibodies are more frequent in children with untreated HCV infection than in controls (88). Enteroviruses have been detected in thyroid tissue of subjects with Hashimoto's thyroiditis (89).…”
Section: Stressmentioning
confidence: 99%